Modelling Housing Investment for Seven Major OECD Countries - Egebo, Thomas (OECD Publishing, 1988)
This paper presents new housing equation estimates for the major seven countries in INTERLINK, the OECD world econometric model. Theoretical and empirical aspects of housing investment behaviour are discussed in a model context. Estimation results using an adjustment model for the stock of houses are presented and discussed, together with simulations comparing the performances of the old and new housing blocks in the model. The results embody an important improvement in understanding the aggregate determination of aggregate residential investment ...
Keywords: Economics